SISTEM FONOLOGI BAHASA MINANGKABAU DI KENAGARIAN SINGKARAK KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - Zurmita, Deni Nofrina; Ermanto, Ermanto; Zulfikarni, Zulfikarni (Jurnal Bahasa dan Sastra, 2013)
This article was written to describe the Minangkabau language phonological system in Kenagarian Singkarak based on (1) the system of vowels, (2) consonant system, (3) diphthong, (4) distribution of vowels, consonants and diphthongs, (5) form syllables. The method used in this research was descriptive method. The data in this study were 200 basic vocabularies of Morris Swades and basic cultural vocabulary. The data was collected with basic techniques such â€œpancingâ€ technique, followed by â€œcakap semukaâ€ technique. The finding theMinangkabau language phonological system in Kenagarian Singkarak research is 5 vocal, 20 consonant, 4 phoneme diphthongs, distribution vocal complete, while distribution consonant consisting of 8 consonants complete and 12 incomplete and distribution diphthong incomplete and form syllables consisting a vowel (V), a vowel and a consonant (VC), a consonant and a vocal (CV) and a consonant, a vowel, a of consonants (CVC). Â  Kata Kunci: fonologi, vokal, konsonan, diftong,